Deformation Characteristics of Existing Twin Tunnels Induced by Double Shield Undercrossing with Prereinforcement: A Case Study in Hangzhou. (17th August 2021) - Wei, Xinjiang; Zhang, Mobao; Ma, Shaojun; Xia, Chang; Liu, Xingwang; Ding, Zhi
Abstract : This paper is based on the case of the earth pressure balance (EPB) shield tunnelling project of the new Metro Line 2 undercrossing the existing Metro Line 1 in the soft soil urban area of Hangzhou. Because the EPB shield must break through a plain concrete wall before undercrossing the existing tunnels, the pipe roof prereinforcement was adopted to stabilize the soil between the existing tunnels and the new shield tunnel. The deformation characteristics of the existing tunnels in the process of double shield undercrossing were discussed. According to the variation of shield position, the settlement development could be divided into three stages: shield approaching subsidence, shield crossing heave, and shield leaving subsidence. The horizontal displacement shows a back and forth variation characteristic consistent with the direction of shield tunnelling. At the junction of tunnel and station, the shield undercrossing caused considerable differential settlement between the existing tunnel and the station. The construction of pipe roof prereinforcement will lead to the presettlement of the existing tunnels. The settlement of the existing tunnels caused by the attitude deviation of pipe roof and grouting disturbance should be reduced in reasonable ranges. In addition, the maximum longitudinal settlement of the existing tunnel during the shield second undercrossing was also discussed. It was considered that the influence of wall breaking is greater than the sequence of shield undercrossing. The driving parameters of shield tunnelling should be optimized before the second crossing.